2023
DOI: 10.1001/jamanetworkopen.2022.55804
|View full text |Cite
|
Sign up to set email alerts
|

Early vs Deferred Non–Messenger RNA COVID-19 Vaccination Among Chinese Patients With a History of Inactive Uveitis

Abstract: ImportanceImproper host response to COVID-19 vaccines could trigger immune-mediated adverse events. The question remains whether COVID-19 vaccination should be postponed until complete remission in patients with uveitis, a preexisting immune-related condition.ObjectiveTo compare recommendations for early and deferred COVID-19 vaccination with respect to uveitis outcomes.Design, Setting, and ParticipantsThis open-label, randomized clinical trial at a large, specialized teaching center for uveitis care in China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The authors found no evidence that uveitis activity or visual acuity at 3 months differed substantially based on the recommendation. 19 Because our patient received an mRNA COVID-19 vaccine, simple comparison is difficult; however, the results of this earlier study may be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found no evidence that uveitis activity or visual acuity at 3 months differed substantially based on the recommendation. 19 Because our patient received an mRNA COVID-19 vaccine, simple comparison is difficult; however, the results of this earlier study may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…If she had received systemic glucocorticoids after vaccination, the VKH disease may not have recurred. Furthermore, Zhong et al 19 showed that compared with the recommendation for deferred vaccination, the recommendation for patients with inactive uveitis to receive early non-mRNA COVID-19 vaccination led to earlier self-reported worsening of symptomatic uveitis. The authors found no evidence that uveitis activity or visual acuity at 3 months differed substantially based on the recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a shorter time to symptomatic uveitis flare in the early vaccination group (HR = 1.68; P = 0.01), though there were no significant differences in objective uveitis activity or visual acuity between the groups at 3 months. It was, therefore, concluded that early non-mRNA COVID-19 vaccination was linked to a higher incidence of symptomatic uveitis worsening, possibly due to reporting bias, but did not affect disease or visual outcomes at 3 months 90 …”
Section: Uveitis-related To Coronavirus Disease 2019 Vaccinationmentioning
confidence: 99%
“…It was, therefore, concluded that early non-mRNA COVID-19 vaccination was linked to a higher incidence of symptomatic uveitis worsening, possibly due to reporting bias, but did not affect disease or visual outcomes at 3 months. 90 In summary, although COVID-19 vaccination has been associated with a broad spectrum of ocular inflammation manifestations, the current evidence remains inconclusive regarding whether these vaccines are truly a cause of de novo disease. However, there appears to be an association with the reactivation of preexisting uveitis.…”
Section: Uveitis-related To Coronavirus Disease 2019 Vaccinationmentioning
confidence: 99%